2020
DOI: 10.1111/1475-4932.12577
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Pecuniary Rewards, Multiple Job‐Holding and the Labour Supply of Creative Workers: The Case of Book Authors*

Abstract: Non‐pecuniary rewards to work, or psychic income, are a pervasive phenomenon in several labour markets, yet they have been little investigated either theoretically or empirically. Creative industries are a particular case where non‐monetary incentives are widely observed. These are also industries where moonlighting commonly occurs because artistic or creative activity is generally low paid, such that workers have to balance their chosen pursuit with another job to make ends meet. In this paper we propose a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Later studies linked it with wages, where Bedi (1998) and Muravyev (2009) observed the wage gaps among moonlighters. Studies have also cited low wages (Dempster-Mcclain and Moen, 1989; Hyder and Ahmed, 2009; Longden and Throsby, 2021; Partridge, 2002) as a determinant.…”
Section: Discussion: a Critical Viewpointmentioning
confidence: 99%
“…Later studies linked it with wages, where Bedi (1998) and Muravyev (2009) observed the wage gaps among moonlighters. Studies have also cited low wages (Dempster-Mcclain and Moen, 1989; Hyder and Ahmed, 2009; Longden and Throsby, 2021; Partridge, 2002) as a determinant.…”
Section: Discussion: a Critical Viewpointmentioning
confidence: 99%
“…Most of the theoretical contributions have discussed the purpose of moonlighting and they have identified four key theoretical motives for moonlighting. Hours constrained motive which explained moonlighting as a result of the underutilization of workers in the primary job (Shishko & Rostker,1976;Krishnan,1990;Kimmel & Conway,1995), financial motive which explained the tendency for moonlighting for additional financial requirements (Guariglia & Kim, 2004;Renna & Oaxaca, 2006;Asravor,2021), heterogeneous jobs motive which explains the moonlighting to perform different interest, skills and human capital attainment (Conway & Kimmel,1992;) and the flexibility motive (Conen & Buschoff, 2021;Longden & Throsby, 2021) which explains the possibility of engaging secondary employment due to the freedom of work schedules being the key four motives for moonlighting. Piasna et al (2021) have found that the key motive of multiple job holding is the quality of primary employment which covers six dimensions of income, flexibility, control of working time, job security, work pressure, unsocial hours, skills and autonomy which covers many of the above aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sometimes, incentives may be used to reinforce motivation (Ashraf & Jack, 2014;Mustafa & Ali, 2019;Wolff et al, 2005;Tumi et al, 2022). However, most studies proved non-monetary rewards highly motivate employees in the higher education and other industries (Sureephong & Dahlan, 2020;Meyer et al, 2022;Mustafa & Ali, 2019;Low & Robertson, 2006;Markova & Ford, 2011;Longden & Throsby, 2021). While the success of every organization is dependent upon the employee's work performance, the best way to ensure employees commitment and loyalty is through motivation.…”
Section: Introductionmentioning
confidence: 99%